2017
DOI: 10.1155/2017/4589214
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Progesterone Receptor Isoform Expression in Pregnant Human Myometrium

Abstract: Background. Regulation of myometrial progesterone receptor (PR) expression is an unresolved issue central to understanding the mechanism of functional progesterone withdrawal and initiation of labor in women. Objectives. To determine whether pregnant human myometrium undergoes culture-induced changes in PR isoform expression ex situ and, further, to determine if conditions approaching the in vivo environment stabilise PR isoform expression in culture. Methods. Term nonlaboring human myometrial tissues were cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 90 publications
1
20
0
Order By: Relevance
“…Furthermore, it has been shown that the onset of labor is associated with increased abundance of PR-A mRNA, and an increase in the PR-A/PR-B expression ratio in term human myometrium [82]. The observation that PR-A mRNA abundance and the PR-A/PR-B expression ratio significantly increased during in vitro incubation is therefore once again consistent with the non-laboring tissue pieces transitioning to a labor-like state as a consequence of in vitro conditions [88]. Performing in vitro experiments using myometrium that is in a state of flux is not ideal, and raises the possibility that the relevant literature may contain findings reported for 'non-laboring' tissue that were in fact obtained with myometrium that was actively transitioning, or had already transitioned to, a laboring phenotype.…”
Section: Tissue Pieces/explant Modelssupporting
confidence: 61%
See 3 more Smart Citations
“…Furthermore, it has been shown that the onset of labor is associated with increased abundance of PR-A mRNA, and an increase in the PR-A/PR-B expression ratio in term human myometrium [82]. The observation that PR-A mRNA abundance and the PR-A/PR-B expression ratio significantly increased during in vitro incubation is therefore once again consistent with the non-laboring tissue pieces transitioning to a labor-like state as a consequence of in vitro conditions [88]. Performing in vitro experiments using myometrium that is in a state of flux is not ideal, and raises the possibility that the relevant literature may contain findings reported for 'non-laboring' tissue that were in fact obtained with myometrium that was actively transitioning, or had already transitioned to, a laboring phenotype.…”
Section: Tissue Pieces/explant Modelssupporting
confidence: 61%
“…In light of these findings, Ilicic et al [88] further examined whether myometrial tissue pieces undergo culture-induced changes in PGR isoform expression that are consistent with transition to a pro-contractile, labor-like phenotype. It was revealed that progesterone receptor A (PR-A) mRNA abundance increased after just 1 h culture, whereas progesterone receptor B (PR-B) mRNA abundance remained constant [88]. The net effect was a statistically significant increase in the PR-A/PR-B expression ratio after just 6 h of in vitro incubation [88].…”
Section: Tissue Pieces/explant Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the brain and the spinal cord, they present a different expression pattern, regulation, and function [31][32][33][34][35]. Generally, given that the PR-B is a more potent transcription activator than the PR-A, the former is the positive regulator of the genomic effects of progesterone, whereas PR-A is mainly a transcriptional repressor [36][37][38].…”
Section: Introductionmentioning
confidence: 99%